Neuroscience Education Begins With Good Science: Communication About Phineas Gage (1823–1860), One of Neurology’s Most-Famous Patients, in Scientific Articles - Schleim, Stephan (Frontiers in Human Neuroscience, 2022)
Phineas Gage is one of the most famous neurological patients. His case is still described in psychology textbooks and in scientific journal articles. A controversy has been going on about the possible consequences of his accident, destroying part of his prefrontal cortex, particularly with respect to behavioral and personality changes. Earlier studies investigated the accuracy of descriptions in psychology textbooks. This is, to my knowledge, the first analysis of journal articles in this respect. These were investigated with regard to four criteria: description of (1) personality changes, (2) psychopathy-like behavior, (3) alternative explanations besides the immediate brain damage, and (4) Gage’s recovery. 92% of articles described personality changes, 52% of a psychopathy-like kind; only 4% mentioned alternative explanations and 16% described Gage’s recovery. The results are discussed in the light of the available historical evidence. The article closes with several suggestions on improving science communication about the famous case.